PENGARUH SELF REGULATED LEARNING TERHADAP MOTIVASI BERPRESTASI SISWA - Faulina Amiliatuz Zahroh; Ika Ratih Sulistiani; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Self-regulated learning is influenced by several factors, one of which is motivation. The role of self-regulated learning and learning motivation is very important in students so that learning objectives are achieved and are able to achieve the desired achievement. This study aims to determine the effects of self-learning, achievement motivation, and self-study on achievement motivation in 4th grade in Mi Tarbiyatul Huda of Malang. This research is quantitative research using survey research methods. The variables in this study are self-regulated learning (independent variable) and student achievement motivation (dependent variable). The sample in this study amounted to 48 students. The data analysis technique in this study used simple linear regression analysis aimed to determine whether or not there was an effect of self-regulated learning on students' achievement motivation. In this study, all calculations used the SPSS_24 program. Based on the results of a simple linear regression analysis, the results were given a significant difference Sig. 0.003 < probability 0.05 (5%). These results indicate that there is an influence between the variables of self-regulated.